The Internal Auditors’ Perception of Blockchain Technology Implementation in Companies’ Business Activities (International Journal of Applied Research in Management and Economics, 2024)
Nowadays, business activities of every company deal with numerous challenges related to various microeconomic, national, and global aspects. Information and communication technologies’ (ICTs’) developments have been crucial in that context, as they disrupt internal business processes, ways of communication, tax services, risk and regulatory functions, and other business aspects. A key game changer new technology, with concrete application in companies, is blockchain technology (BCT). BCT enables automation, acceleration, transparency, traceability, and increased security of numerous business processes. BCT and related disruptions in the ways of working do not bypass internal audit function, as an internal corporate governance monitoring mechanism, either. As a result, contemporary internal auditors must be adaptable, agile, and proactive to be able to audit and consult about BCT enabled companies’ business activities. Thus, the research problem was related to internal auditors’ perception of implementing BCT in their companies’ business activities. Based on the conducted critical literature review, we developed the following research hypothesis: internal auditors who work in a company where BCT is already implemented in its business activities will have a favorable view of the implementation of BCT in the company’s business activities compared to internal auditors whose company does not currently use and have no plans to implement BCT in the following years. To test research hypothesis, survey research was conducted among internal auditors in Croatia. We obtained responses from 77 internal auditors from different sectors. Collected data were analysed by applying multiple regression analysis. Obtained results indicated that there exists a statistically significant relationship between internal auditors’ perception of implementing BCT and companies’ application level of BCT.